Determinants of routine immunization coverage among under-five children in Jigawa state, Nigeria - Abdulwali Sabo; Majdi M. Alzoubi; Auwalu Garba; Abdulhamid Yaro Saidu; Usman Sunusi Usman; Ibrahim Musa Saulawa; Khalid Al-Mugheed; Sally Mohammed Farghaly Abdelaliem (BMC Public Health)
Abstract Introduction Immunization is a cost-effective public health strategy for reducing the morbidity and mortality associated with infectious diseases. However, in recent years, the country has reportedly seen a steady decline in immunization coverage. Methods A cross-sectional study was carried out among parents and caregivers of under-five children. A total of 400 participants were randomly selected using a simple random sampling approach. Data were collected through interviewer-administered questionnaires to evaluate the study variables. Statistical analyses involved descriptive statistics and multiple logistic regression using the Statistical Product and Service Solution (SPSS) version 29. Results Awareness of routine immunization was reported by 81.5% of parents/caregivers, with 65.3% accurately identifying its definition. At the time of data collection, only 22.2% of their children had achieved complete immunization status, with 74.0% citing the long distance to healthcare facilities as the main obstacle for their child to complete immunizations. Additionally, only fathers’ monthly income (OR = 1.71, P = 0.002) and perceived waiting time (OR = 0.41, P = 0.009) were significant predictors of complete immunization. Conclusion The study indicates the need for a combination of short-term strategies, such as providing some incentive to encourage parent participation and establishing digital health records to improve real-time tracking of immunization coverage, as well as long-term strategies, such as improving infrastructure and service delivery at health centres to reduce waiting time and employing innovative technology to expand digital immunization records and reminder systems for targeted interventions.